The ecological significance of secondary seed dispersal by carnivores. Issue 2 (23rd February 2017) - Hämäläinen, Anni; Broadley, Kate; Droghini, Amanda; Haines, Jessica A.; Lamb, Clayton T.; Boutin, Stan; Gilbert, Sophie
Abstract: Animals play an important role in the seed dispersal of many plants. It is increasingly recognized, however, that the actions of a single disperser rarely determine a seed's fate and final location; rather, multiple abiotic or animal dispersal vectors are involved. Some carnivores act as secondary dispersers by preying on primary seed dispersers or seed predators, inadvertently consuming seeds contained in their prey's digestive tracts and later depositing viable seeds, a process known as diploendozoochory. Carnivores occupy an array of ecological niches and thus range broadly on the landscape. Consequently, secondary seed dispersal by carnivores could have important consequences for plant dispersal outcomes, with implications for ecosystem functioning under a changing climate and across disturbed landscapes where dispersal may be otherwise limited. For example, trophic downgrading through the loss of carnivores may reduce or eliminate diploendozoochory and thus compromise population connectivity for lower trophic levels. We review the literature on diploendozoochory and conclude that the ecological impact of a secondary vs. primary seed disperser depends on the relative dispersal distances, germination success, and the proportion of seeds exposed to secondary dispersal by carnivores. None of the studies up to present day have been able to rigorously assess the ecological significance of this process. We provide a framework of the components that determine the significance of diploendozoochory across systems and identify the components that must be addressed in future studies attempting to assess the ecological importance of diploendozoochory.